2016
DOI: 10.1108/ijcma-10-2015-0070
|View full text |Cite
|
Sign up to set email alerts
|

Conflict management and age in service professions

Abstract: Purpose -The purpose of this study was to examine age differences in conflict management strategy use, effectiveness, and in exposure to customer stressors in service interactions.Design/methodology/approach -Moderated regression and mediation analyses were conducted to test hypotheses in a sample of 444 German service employees from different service branches with frequent customer contact.Findings -Results revealed that older service employees experienced fewer customer stressors. Customer stressors mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 81 publications
(136 reference statements)
2
15
0
Order By: Relevance
“…This suggests that life experience, and not just job experience, is important when determining the use of emotional labour strategies. This is in line with previously reported findings where job age was shown to have little impact on the use of stress management strategies and burnout (Johnson et al, 2013) or conflict management and burnout (Beitler, Machowski, Johnson & Zapf, 2016), again suggesting that it is life experience that is more important than job experience. Practically this is important, if life experience means older individuals have the appropriate skills in terms of emotion regulation to match the requirements of the service sector, then previous job related experience may be less important than life experience when matching applicants to job requirements.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This suggests that life experience, and not just job experience, is important when determining the use of emotional labour strategies. This is in line with previously reported findings where job age was shown to have little impact on the use of stress management strategies and burnout (Johnson et al, 2013) or conflict management and burnout (Beitler, Machowski, Johnson & Zapf, 2016), again suggesting that it is life experience that is more important than job experience. Practically this is important, if life experience means older individuals have the appropriate skills in terms of emotion regulation to match the requirements of the service sector, then previous job related experience may be less important than life experience when matching applicants to job requirements.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, it is necessary to address the potential influence of cultural characteristics on organizational behaviour (Brodbeck, Frese, & Javidan, 2002) in a sample of German service employees. Beitler et al (2016) discuss that Germany ranks very high on sociocultural dimensions such as assertiveness, uncertainty avoidance, and high on performance orientation (Brodbeck & Frese, 2007;Brodbeck et al, 2002) and report that despite the cultural differences between Germany, China, and the USA similar age effects are reported for conflict management. Similarly, our results about emotion regulation are in line with studies conducted in different cultural contexts.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…And even more so, the behaviour manifested in this episode is not necessarily aggressive but can also be constructive as employees in conflict may, for example, also solve the problem or seek a compromise (Pondy, 1967;Thomas, 1992;Van de Vliert, 1997). In line with this, several studies (e.g., Beitler, Machowski, Johnson, & Zapf, 2016;de Dreu, Evers, Beersma, Kluwer, & Nauta, 2001) show that problem solving is amongst the most frequently used conflict management strategies whereas the opposite can be found for bullying conflicts (Ayoko, Callan, & Härtel, 2003). Consequently, the obvious and frequent occurrence of negative social behaviours, which is an explicit part of workplace bullying, is not a defining characteristic of interpersonal conflicts and can be separated from task and relationship conflicts by confirmatory factor analysis (Leon-Perez et al, 2014).…”
Section: Negative Social Behaviourmentioning
confidence: 80%
“…To the contrary, a meta‐analysis showed that older employees even outperform younger ones on organizational citizenship behavior directed toward the task, while there was no relationship between age and core task performance in general (Ng & Feldman, ). In the service sector, there is growing evidence that older employees show better performance than their younger colleagues, when coping with stressful customer situations (Beitler, Machowski, Johnson, & Zapf, ; Dormann, Brod, & Engler, ). Yet, despite the lack of supporting evidence, age stereotypes continue to influence decisions at the workplace, leading to adverse employment conditions for older workers (Posthuma & Campion, ; Truxillo & Fraccaroli, ).…”
Section: Work‐related Age Stereotypesmentioning
confidence: 99%